Electrochemical properties of Cu4[PhN3C6H4N3(H)Ph]4(μ-O)2, a tetranuclear Copper(II) complex with 1-phenyltriazenido-2-phenyltriazene-benzene as ligand - Hermann, Alessandro; da Silva, Lucinei Stechmann; Peixoto, Carlos Roberto de Menezes; de Oliveira, Adriano Bof; Bordinhão, Jairo; Hörner, Manfredo (Eclética Química, 2008)
Bis-(μ2-oxo)-tetrakis[1-feniltriazene-1,3-diil)-2-(phenyltriazenil)benzene copper(II) is a tetranuclear complex which shows four Cu(II) ions coordinated by four 1,2-bis(phenyltriazene)benzene bridged ligands, with one diazoaminic deprotonated chain, and two O2- ligands. The complex reduces at E1/2 = -0.95 V vs Fc+/Fc, a two electrons process. Cyclic voltammetric and spectroelectrochemical studies showed a reversible process. When immobilized on carbon paste electrode, the complex electrocatalyses the reduction of O2 dissolved on aqueous solution at –0.3 V vs SCE potential. The obtained current shows linearity with O2 concentration.